Evaluation of yield, yield components and some quality traits of tuber of potato (Solanum tuberosum L.) under different weed and nutritional management practices - Hooshmand Amjadi; Gholamreza Heidari; Sirwan Babaei; Zahed Sharifi (Frontiers in Plant Science)
Potato (Solanum tuberosum L.) production requires effective nutrient and weed management strategies to enhance tuber yield and quality while minimizing the environmental impact of chemical inputs. This study investigated the effects of various weed and nutrient management practices on potato tuber yield, yield components, and quality traits. The experiments were conducted over two years (2019–2020) at the University of Kurdistan’s research farm in the Dehgolan Plain, using a split-plot based on randomized complete block design with four replicates. Main plot treatments included a control (no fertilizer), complete chemical fertilizer (based on soil testing), foliar application of edible mushroom powder, and seaweed extract. Subplot treatments focused on weed control methods, consisting of a control (no weed control), chemical herbicides (metribuzin + paraquat), a biological herbicide, and manual weeding (weed-free). The highest tuber yield was achieved with the combination of metribuzin and paraquat herbicides alongside manual weeding in the complete fertilizer regimen, yielding 25 and 23.2 t ha⁻¹, respectively. Treatments with edible mushroom powder resulted in a 32% increase in tuber counts but a 21% decrease in individual tuber weights compared to the control. Tuber quality was significantly affected, with phosphorus concentration peaking at 0.26% under the complete fertilizer regimen, whether paired with manual weeding or the biological herbicide. Additionally, reducing sugars were highest in the complete fertilizer and chemical weed management treatments, indicating potential implications for tuber processing quality. These findings suggest that an integrated approach combining complete chemical fertilizer application with effective weed control maximizes both total yield and nutrient concentrations in potatoes. The results provide valuable insights for developing sustainable potato production practices that balance yield optimization with environmental stewardship.